A crosstalk of circadian clock and alternative splicing under abiotic stresses in the plants - Fan, Tao; Aslam, Mehtab Muhammad; Zhou, Jian-Li; Chen, Mo-Xian; Zhang, Jianhua; Du, Shenxiu; Zhang, Kai-Lu; Chen, Yun-Sheng (Frontiers in Plant Science, 2022)
Circadian clocks are internal time-keeping mechanism which synchronize physiological adaptation of an organism to its surrounding based on day and night transition in a period of 24 hours, suggesting circadian clocks provides fitness by adjusting environmental stresses. Circadian clocks are driven by positive and negative elements which regulate transcriptionally and post-transcriptionally. Alternative splicing is a crucial transcriptional regulator capable of generating large number of mRNA transcripts from limited number of genes, leads to proteome diversity, involved in circadian dealing with abiotic stresses. Over the past decade, alternative splicing and circadian control has been suggested to coordinately regulate plant performance under simultaneously fluctuating environmental conditions. However, only few reports are seldom reported the regulatory mechanism of this crosstalk. Based on the emerging evidence, this review elaborates the existed links between circadian and alternative splicing in response to abiotic stresses, suggesting an uncovered regulatory network intervened among circadian, alternative splicing, and abiotic stresses. Therefore, this regulation possibly connected in both shoot and root clock regulation in synchronization with the surrounding environment, essential for plant growth and development.